REKONSTRUKSI KONSEP PENDIDIKAN AGAMA ISLAM DALAM PERSPEKTIF FILOSOFIS DAN PRAKTIS - Muhammad Faisal; Iskandar Mirza; Mochamad Yaqub Sulaeman (STKIP Subang, 2026)
Islamic Religious Education (IRE) as one of the core subjects in Indonesia's national education system faces serious challenges in the contemporary era, both conceptually and implementatively. This paper aims to explore and analyze efforts to reconstruct the concept of IRE through philosophical and practical approaches, by examining the thoughts of several relevant Islamic education scholars. The method used is library research with a descriptive-analytical approach. The results show that the reconstruction of IRE needs to rest on three main pillars: first, the reorientation of educational goals from a normative-dogmatic approach toward a humanistic-dialogical one; second, the transformation of learning methodology from knowledge transmission to contextual understanding construction; and third, the revitalization of the role of IRE teachers as agents of moral as well as intellectual change. This reconstruction is a fundamental effort to restore the true spirit of Islamic education in forming people who are knowledgeable, have noble character, and are able to answer the challenges of the times.